Presence of Anaplasma spp. and their associated antibodies in the Swedish goat population - Lysholm, S.; Ådén, F.; Aspán, A.; Högberg, A.; Wensman, Jonas Johansson; Omazic, A. (MDPI, 2023)
Anaplasmosis is a tick-borne disease that has a severe impact on livestock production and welfare. The aim of this pilot study was to investigate the presence of Anaplasma spp. and associated antibodies in a subset of the Swedish goat population. In 2020, six goat herds located in different parts of Sweden were visited and whole blood and serum samples were collected. The whole blood samples (n = 40) were analysed for the presence of Anaplasma phagocytophilum, A. ovis and A. capra using quantitative and conventional polymerase chain reaction (PCR). The serum samples (n = 59) were analysed for the presence of antibodies to Anaplasma spp. using a commercial competitive enzyme-linked immunosorbent assay, and the same analysis was carried out on additional serum samples previously collected in 2018, 2019 and 2020 (n = 166). One goat (2.5%) tested positive for the presence of A. phagocytophilum genetic material, while the seropositivity rate ranged from 20 to 71%, depending on the surveyed year and area. These results indicate widespread exposure to Anaplasma spp. in the Swedish goat population. To inform future risk assessments and control efforts, further research is warranted to determine the prevalence of anaplasmosis and its impact on goat farming in Sweden.